Language Assessment Literacy in EFL Edupreneurship Among Lecturers at Muhammadiyah University of Makassar and Samarkand Institute - Hambali, Uyunnasirah; Natsir, Ratu Yulianti; Akib, Erwin; Valeryevna, Petrosyan Nelya (Pandawan, 2024)
Language Assessment Literacy (LAL) is a crucial competency for language teachers, encompassing the knowledge and skills required to effectively conduct assessment activities. This research aims to explore the perceptions of EFL lecturers at Muhammadiyah University of Makassar and Samarkand Institute regarding different types of LAL, and how technological innovations and digital tools can enhance these skills. The study utilized a purposive sampling technique to select ten lecturers from both institutions, who participated in an online questionnaire focusing on two main categories: